Neurocognitive Effects of Obesity and Bariatric Surgery. (19th August 2015) - Spitznagel, Mary Beth; Hawkins, Misty; Alosco, Michael; Galioto, Rachel; Garcia, Sarah; Miller, Lindsay; Gunstad, John
Abstract: This review paper will discuss the recent literature examining the relationship between obesity and neurocognitive outcomes, with a particular focus on cognitive changes after bariatric surgery. Obesity is now recognized as an independent risk factor for adverse neurocognitive outcomes, and severely obese persons appear to be at even greater risk. Bariatric surgery is associated with rapid improvements in cognitive function that persist for at least several years, although the mechanisms underlying these improvements are incompletely understood. Assessment of cognitive impairment in bariatric surgery patients is challenging, and improved methods are needed, as poorer performance on neuropsychological tests of memory and executive function leads to poorer clinical weight outcomes. In addition to its clinical importance, further study in this area will provide key insight into obesity‐related cognitive dysfunction and clarify the possibility of an obesity paradox for neurological outcomes. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.